Atherosclerosis: An Integrative East-West Medicine Perspective. (5th April 2012) - Xu, Hao; Shi, Dazhuo; Chen, Keji
Abstract : Recent understanding of atherosclerosis and coronary heart disease has shifted the focus from lumen stenosis to vulnerable plaque, from lipid deposit to inflammatory reaction, and from vulnerable plaque to vulnerable patient. This has led to a new direction of treatment consisting of intervening the inflammatory reaction, stabilizing the vulnerable plaque, inhibiting thrombosis after plaque rupture, and treating the vulnerable patient instead of treating lumen stenosis. This seems to mirror the traditional Chinese medicine (TCM) focus on prevention and on the vulnerable patient with treatment matched to the pattern dysfunction and dysregulation using the Chinese herbal medicine multitargeted approach. Given the convergence of both the East and the West conceptualization of atherosclerosis, it is hopeful that the integrative East-West approach will facilitate early detection and more effective treatment of the vulnerable patients with coronary heart disease.